Timber traceability and final destination: lessons learned from a forest governance process in the Ecuadorian Amazon - Reyes Morán, Héctor Fernando (2019)
With the implementation of the National Strategy for Sustainable Forest Development of the year 2000 and especially with the regulations of MFS of the humid forest, practices in Sustainable Forest Management (MFS) in Ecuador began. In the Ecuadorian Amazon, several authors have estimated that the use of wood contributes on average between 14 and 21% of the total monetary income in rural households. In this context, a forest governance process was developed in the province of Napo, which began in 2009 when the Napo Forest Board was established and promoted a participatory governance process. The main purpose of this study was to understand to what extent the existing standards, accompanied by the control and traceability of wood at the final destination, have an impact on the way in which the actors interact with each other during the harvesting and commercialization of Forest Producers.